Identifying Market-Driven Communication Competencies for English for Management Curriculum Development: An Exploratory Study - Cok Istri Agung Sri Wulandari; Ni Putu Intan Permatasari; Ida Ayu Fortuna Ningrum; A.A. Sg. Candra Permatasari (EDUJAVARE: International Journal of Educational Research, 2026)
The increasing demand for workplace-ready graduates in today's globalized business environment has highlighted the need for higher education institutions, particularly English for Management (EfM) programs. This study aimed to identify market-driven communication competencies required by management graduates and examine their implications for curriculum development. An exploratory mixed-methods design was employed involving 22 industry practitioners, 11 academic stakeholders, and 50 Management students at Universitas Pendidikan Nasional. Data were collected through semi-structured interviews, questionnaires, and curriculum document analysis. Qualitative data were analysed using thematic analysis, while quantitative data were examined using descriptive statistics. The findings revealed six essential communication competency domains: Professional Communication, Intercultural Communication, Leadership Communication, Customer Relations Communication, Digital Communication, and Negotiation and Problem-Solving Communication. The study also identified significant gaps between workplace expectations and existing curriculum provisions, particularly in digital, intercultural, customer relations, and negotiation competencies. The study concludes that a market-driven approach is necessary for EfM curriculum development. The proposed Bali Market-Driven English Communication Competency Framework (BM-ECCF) provides an evidence-based foundation for curriculum redesign aimed at enhancing graduate employability and workplace readiness.